Multiculturalism Insight Based on Qur’an and its Relevance to Plurality in Indonesia - Falihin, Dalilul; Zulaeha, Zulaeha; Muzzammil, Ahmad; Mude, M. Saleh (Jurnal Adabiyah, 2024)
The article reveals the concept of multiculturalism in the Koran. Multiculturalism is necessary for dialogue, dialogue patterns, interaction, and cross-faith cooperation. And their significance within the pluralistic framework of Indonesian society. For this reason, various approaches to studying the Quran are applied to uncover the true meaning of the Koran. For tracking the relevance of Qur’anic concepts to the context of Indonesian pluralism, the Living Qur’an approach is used. Based on these approaches, diversity is a necessity that must be proactive and ethical in an ongoing dialogue, not a reactive, artificial, and sentimental dialogue. Another finding is utilizing historical treasures in Islam called taqiyya. Even though Muslims (Shia-Sunni) differ in their position on taqiyya, all acknowledge its existence and use it to address diversity for harmony and tolerance. Abstrak Artikel Mengkaji secara mendalam konsep tentang multiculturalism di dalam al-Quran. Multikulturalitas sebagai keniscayaan, mendialogkan multicultural, pola dialog, interaksi dan kerjasama lintas keyakinan, serta relevansinya dengan konteks Indonesia yang majemuk. Untuk itu, berbagai pendekatan dalam studi Qur’an diterapkan dalam menguak Makna sejati multicultural dari al-Qur’an. Untuk menemukan relevansi konsep-konsep Qur’an dengan konteks kemajemukan Indoensia maka diterpakan pendekatan living Quran. Berdasarkan pendekatan-pendekatan tersebut, keragaman merupakan sebuah keniscayaan yang harus didialogkan secara berkelanjutan yang pro-aktif dan beretika, bukan dialog yang reaktif, semu, dan sentiment. Temuan lainnya adalah memanfaatkan khazanah sejarah dalam Islam yang disebut taqiyyah. Meskipun umat Islam berbeda dalam memosisikan taqiyyah tersebut, namun semua mengakui eksistensi dan penggunaannya untuk menyikap keragaman demi terwujudnya harmoni dan toleransi.